Battery Thermal Management System for Electric Vehicles (Indian Journal of Software Engineering and Project Management (IJSEPM), 2023)
Electrical vehicles (EVs) as a result of their rapid evolution and growing popularity, zero-emission, and high tank-to-wheel efficiency. Though, some features, particularly those relating to battery performance, cost, lifetime, and protection, restrict the development of the electrical car. In order to operate at peak efficiency under various circumstances, battery management is therefore required. The BTMS is essential for controlling the thermal performance of the battery. The BTMS technologies include heating, air conditioning, liquid cooling, direct refrigerant cooling, phase change material (PCM) cooling, and thermoelectric cooling. Performance, weight, size, cost, dependability, safety, and energy consumption are trade-offs analyzed for these systems. According to the analysis the system is made up of two coolant loops, one refrigeration loop, and one cabin HVAC loop. The batteries, drivetrain, and cabin all contribute to the thermal burden. The model of these system is been built in the software MATLAB/SIMULINK. Based on the outcomes of the simulation, BTMS is crucial for regulating battery thermal behavior. Through the integration of the simulation model with battery thermal and ML models, next research might be more thorough and precise.